Gelombang Detonasi Marginal Campuran Bahan Bakar Hidrogen, Oksidizer Udara dan Oksigen dengan Pengencer Argon - , ARI DWI PRASETIYO, Dr. Eng. Jayan Sentanuhady, ST., M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the combustion process, detonation wave is generated when the reaction wave coincides with the shock wave at supersonic speed. Shock wave propagated at high pressure, it would be dangerous to human if detonation accidents occur. In conditions of rich mixture or lean mixture, the detonation wave may propagate by using one detonation cell only, this condition is usually called as detonation marginal. By knowing the detonation limits in marginal areas, the consequences of an accident due to detonation can be avoided or minimized. In these experiments, various concentrations of hydrogen gas mixture with air and oxygen oxidizer is used as the main fuel and argon added to control the reaction rate. The fuel mixture in the circular cross section of detonation test tube is at room temperature condition and an initial pressure of 100 kPa. The experimental results showed characteristics of shock wave velocity and pressure on marginal detonation lower than the Ordinary. This is seen in the case of hydrogen fuel air mixture, which the pressure reaches 11.56 times from the initial pressure and velocity reaches 0.76 VCJ. The ordinary detonation pressure value can reach 15-16 times from the initial pressure and velocity approaching the value of 0.92 VCJ. The addition of argon gas into the fuel mixture will narrow limits marginal areas as a result of a decrease in the rate of the combustion reaction. Keyword: Combustion, Detonation, Marginal, Reaction Wave, Shock Wave